Pulse train stability in passively Mode-locked Erbium-doped fiber laser with a nonlinear polarization rotation - Nur Ameelia Abdul Kadir; Nurul Alina Afifi Norizan; Azura Hamzah (Institute of Advanced Engineering and Science, 2019)
A nonlinear polarization rotation technique-based mode-locked erbium-doped fiber laser has been experimentally demonstrated using a 0.75 m long highly concentrated erbium-doped fiber as the gain medium. With unintentional polarization dependent loss induced by twisting single-mode fiber in an intracavity polarization controller, the optical output of the laser shifts from continuous wavelength to modelocked soliton pulse. A stable and cleaner pulse with a repetition rate of 15.32 MHz laser wavelengths and a pulse energy of 0.496 nJ with optical signal-to noise ratio of more than 33 dB are successfully obtained using a simple ring cavity.